Empowerment of Health Volunteers for Optimizing MCH and Family Planning (KB) Services During the COVID-19 Pandemic in Nagari Kambang Utara - Yulizawati, Yulizawati; Syah, Nur Afrainin; Firdawati, Firdawati; Maputra, Yantri; Yulika, Marzatia; Afrah, Rahmayani; Lubis, Siska Ilannur; Aprila, Prety Zinta; Putri, Viorika Marsafa (Journal of Midwifery, 2024)
During the Covid-19 pandemic, there was a decrease in the availability of Maternal and Child Health (MCH) and contraceptive services, reduced access to services, and increased risk of infection for health workers. coverage of antenatal care, contraception and immunization has decreased significantly. Nagari Kambang Utara also experienced a decrease in the coverage of MCH services during the pandemic. Therefore, to support the recovery of maternal and child health services during the pandemic, health workers need to work together with cadres to reach all communities in order to get the health services they need. Empowering cadres is a step that is needed to help optimize maternal and child health services during the COVID-19 pandemic. The method of activities carried out is by using participatory methods from the target group, namely the health partners and the community of Nagari Kambang Utara. The activity began with conducting a workshop related to the formation of health cadres for the Nagari Kambang Utara. After the workshop was carried out, it was continued with data collection for cadres and training of health cadres in accordance with the work focus, namely cadres of pregnant women, maternity mothers, postpartum mothers, breastfeeding mothers, infant and toddler cadres and family planning cadres. The proposing team and partners agreed to work together to optimize the performance of health cadres by conducting cadre training and evaluation and agreed to carry out cooperation in the next 5 years. The results of this activity are expected to increase the achievement of MCH and family planning services and decrease MMR and IMR.